Effect of Al addition on the single and cyclic ablation properties of C/C–SiC composites. Issue 4 (15th February 2023) - Zhang, Haijun; Liu, Lei; Feng, Wei; Guo, Yongchun; Han, Qinxin; Tang, Chengwei; Wang, Xinyu; Xie, Yixin
Abstract: This article focuses on the damage behavior and mechanism of aluminum addition on reactive melt infiltrated C/C–SiC composites in single and cyclic ablation environments. Plasma ablation tests were performed on C/C–SiC composites containing 20 wt % and 40 wt % aluminum respectively. Coupled with TMA, XRD, SEM and EDS, the results showed that composites with 40 wt % Al had better ablation resistance during the cyclic ablation, while the composites with 20 wt % Al had excellent ablation damage resistance during a single ablation. This difference was due to higher number of microcracks formed inside the composites containing 40 wt % Al than 20 wt % Al, the lower specimen surface temperature during ablation, and the thermal stresses can be released by pore crack expansion during gas reciprocal loading. While in the single continuous loading of gas, the 20 wt % Al composite formed a protective oxide layer with smaller pores and fewer gas and oxygen entry channels, resulting in good resistance to ablation.